Hypomethylating agents in combination with venetoclax for acute myeloid leukemia: Update on clinical trial data and practical considerations for use. Issue 3 (13th December 2018) - Mei, Matthew; Aldoss, Ibrahim; Marcucci, Guido; Pullarkat, Vinod
Abstract: One of the most promising developments in therapy for acute myeloid leukemia (AML) in recent years has been the combination of hypomethylating agents (HMA, either decitabine or 5‐azacytidine) with the Bcl‐2 inhibitor venetoclax (VEN). Although both classes of drugs have single‐agent activity in AML, the combination has resulted in high rates of complete remission (CR) both in the frontline and relapsed settings suggesting synergy between these two agents. Recent data have suggested that CR + CR with incomplete count recovery rate may exceed 70% for frontline VEN‐HMA. Moreover, this activity has been observed across various genetic subtypes of AML including those known to have very poor response to conventional chemotherapy. Although VEN has only recently obtained FDA approval for treatment of AML, there has been increasing on and off‐label use of this combination given its striking efficacy and excellent toxicity profile. In this article, we summarize the current available data on this combination and offer practical guidelines for management of patients receiving VEN‐HMA. Our recommendations are based on protocol guidelines, published data from clinical trials as well as from analysis of real world evidence from patients treated with this combination.